Addition of granulosa cells collected from differential follicle stages supports development of oocytes derived from porcine early antral follicles - Ai Ishiguro; Yasuhisa Munakata; Koumei Shirasuna; Takehito Kuwayama; Hisataka Iwata (Reproductive Medicine and Biology, 2019)
Abstract Purpose Improvement of in vitro oocyte growth by addition of granulosa cells derived from differential developmental stages of follicles. Methods Granulosa cells (GCs) collected from either early antral follicles (EAFs) or antral follicles (AFs) were added to oocyte‐granulosa cell complexes (OGCs) derived from EAFs, and the in vitro growth of the oocytes was evaluated. Results Granulosa cells were incorporated into OGCs to form new OGCs within 2 days of culture. After 14 days of culture, the number of GCs surrounding oocytes was similar among the three OGCs conditions (unmanipulated “natural OGCs,” “EAF‐GCs add OGCs,” and “AF‐GCs add OGCs”), whereas the survival rate of the GCs and diameter of oocytes grown in vitro were the greatest for “AF‐GCs added OGCs.” After parthenogenetic activation, developmental rate till the blastocyst stage tended to be higher for “AF‐GCs add OGCs” compared with other groups. Addition of AF‐GCs significantly increased a hypoxic marker (pimonidazole staining) and increased the lipid content in oocytes grown in vitro compared with unmanipulated OGCs. Conclusion Addition of GCs derived from more advanced stages of follicles to the OGCs changes the metabolism of oocytes and is beneficial for in vitro growth of oocytes derived from EAFs.